Phocine Distemper Outbreak, the Netherlands, 2002 - Rijks, Jolianne M.; Van de Bildt, Marco W.G.; Jensen, Trine; Philippa, Joost D.W.; Osterhaus, Albert D.M.E.; Kuiken, Thijs
During the 2002 phocine distemper epidemic, 2,284 seals, primarily harbor seals (Phoca vitulina), were found stranded along the Dutch coast. Stranding pattern varied with age, sex, state of decomposition, wind, and location. Cumulative proportion of deaths (54%) was comparable to that in the first reported epidemic in 1988.